Aging and Loving : Christian Love and Sexuality in Later Life - Childs, James M. (Book collections on Project MUSE., 2021)
In Aging and Loving: Christian Love and Sexuality in Later Life, James Childs addresses the social, ethical, physical, and spiritual issues related to sexuality and aging. The book is written for various professionals who minister to the aged (pastors, chaplains, other care providers), for the aging and aged themselves, and for their families. The book provides an ethical account of Christian love that liberates as it engages the special issues of sexuality in later life.